An iron hand over cancer stem cells. Issue 8 (3rd August 2017) - Hamaï, Ahmed; Cañeque, Tatiana; Müller, Sebastian; Mai, Trang Thi; Hienzsch, Antje; Ginestier, Christophe; Charafe-Jauffret, Emmanuelle; Codogno, Patrice; Mehrpour, Maryam; Rodriguez, Raphaël
Abstract: The paradigm of cancer stem cells (CSCs) defines the existence of cells exhibiting self-renewal and tumor-seeding capacity. These cells have been associated with tumor relapse and are typically resistant to conventional chemotherapeutic agents. Over the past decade, chemical biology studies have revealed a significant number of small molecules able to alter the proliferation of these cells in various settings. The natural product salinomycin has emerged as the most promising anti-CSC agent. However, an explicit mechanism of action has not yet been characterized, in particular due to the pleiotropic responses salinomycin is known for. In this punctum, we describe our recent discovery that salinomycin and the more potent synthetic derivative we named ironomycin sequester lysosomal iron. We found that these compounds, by blocking iron translocation, induce an iron-depletion response leading to a lysosomal degradation of ferritin followed by an iron-mediated lysosomal production of reactive oxygen species (ROS) and a cell death pathway that resembles ferroptosis. These unprecedented findings identified iron homeostasis and iron-mediated processes as potentially druggable in the context of CSCs.